Advances in the study of HSP70 inhibitors to enhance the sensitivity of tumor cells to radiotherapy - Du, Sihan; Liu, Ying; Yuan, Yuan; Wang, Yuran; Chen, Yanfang; Wang, Shuai; Chi, Yuhua (Frontiers in Cell and Developmental Biology, 2022)
The 70 kDa heat shock protein (HSP70) is one of the most conserved proteins and a ubiquitous molecular chaperone that plays a role in the folding, remodeling, and degradation of various proteins to maintain proteostasis. It has been shown that HSP70 is abundantly expressed in cancer and enhances tumor resistance to radiotherapy by inhibiting multiple apoptotic pathways, such as interfering with the cellular senescence program, promoting angiogenesis, and supporting metastasis. Thus, HSP70 provides an effective target for enhancing the effects of radiation therapy in the clinical management of cancer patients. Inhibition of HSP70 enhances the radiation-induced tumor-killing effect and thus improves the efficacy of radiotherapy. This article reviews the sensitivity of Hsp70 and its related inhibitors to radiotherapy of tumor cells.